Deprivations and Inequities in Cities Viewed Through a Pandemic Lens - Boza-Kiss, Benigna; Pachauri, Shonali; Zimm, Caroline (Frontiers in Sustainable Cities, 2021)
The COVID-19 pandemic brought a halt to life as we knew it in our cities. It has also put a magnifying glass on existing inequalities and poverty. While everyone has been facing the pandemic’s risks, the lived challenges of the lockdowns have been felt most acutely by the poor, the vulnerable, those in the informal sector, and without savings and safety nets. Here, we identify three ways that the COVID-19 pandemic and related containment measures have exacerbated urban inequalities and how subsequent recovery measures and policy responses have tried to redress these. First, lockdowns amplified urban energy poverty, while recovery measures and policies offer an opportunity to address entrenched inequalities in shelter and energy access. Second, preexisting digital divides even within well-connected cities have translated into inequalities in preparedness for living through the lockdown, but digitalization strategies can enhance equity in access to e-services, online work and education for all in the future. Third, slum dwellers in the world’s cities have been particularly hard hit by the pandemic and lockdown measures, but the spotlight on them provides further impetus for slum upgradation efforts that through improved access to infrastructure can improve living conditions and provide more secure livelihoods.